Green's skeletal trauma in children - Gregory A. Mencio; Marc F. Swiontkowski (Elsevier/Saunders, 2015)
Obtain the best outcomes from the latest techniques with help from a "who's who" of pediatric orthopaedic trauma experts! Considered as the "go-to" reference for orthopaedic trauma surgeons and pediatric orthopaedic trauma surgeons, Green’s Skeletal Trauma in Children presents practical, focused guidance on managing traumatic musculoskeletal injuries in children and adolescents. It emphasizes the unique aspects of children's fractures in terms of epidemiology, mechanisms, management, and the challenges of treating the skeletally immature patient. State-of-the-art coverage includes crucial chapters on skeletal trauma related to child abuse, anesthesia and analgesia, management of children’s fractures, and outcome measures and rehabilitation